Exploring Online-to-Offline Friendships: A Netnographic Study of Interpersonal Communication, Trust, and Privacy in Online Social Networks - Amelia, Syfa; Wibowo, Arif Ardy (CHANNEL: Jurnal Komunikasi, 2023)
Online friendship has become common between generations, especially among Gen Z and Millennials, and some friendships transition from online to offline, which requires disclosing their offline identities. Despite the risks involved, Online Social Networks (OSNs) are essential daily and provide self-expression, social pleasure, and networking opportunities. Privacy is a complex concept with different definitions, and interpersonal communication can be private but can become public depending on the context. Self-disclosure and trust are essential factors in online friendships. This study used netnography to study online consumer-based communities, particularly volleyball fans. We conducted observations, literature reviews, and interviews with informants who had experienced shifting from online friendships to offline ones. We analyzed the data descriptively using the theories of trust and self-disclosure. Participants connect with others who share the same interest in volleyball. They both use pseudonyms to protect their privacy but occasionally post pictures with censorship on their faces due to anxiety over privacy and online crime. They both establish trust with their online friends by analyzing their reputation, performance, mutual friends, interaction, and persona before extending their friendship from online to offline. The study found eight communication patterns that create trust, such as talking about common interests and exchanging personal information, and suggests opportunities for further research on comparing different age and gender groups and exploring communication patterns in other social media platforms.